Construction of Empirical Models of Complex Oscillation Processes with Non-Multiple Frequencies Based on the Principles of Genetic Algorithms - Mykhailo Horbiychuk; Olha Bila; Nataliia Lazoriv (Energy Engineering and Control Systems)
A method for constructing the empirical models of complex processes has been developed on the basis of genetic algorithms which, compared to the inductive method of self-organization of models, significantly reduces computer time for their implementation. An approach has been used that allows a complex model to be considered as a composition of three components, i.e. a linear trend, an oscillatory component with non-multiple frequencies and a regression equation which simplifies the process of building complex models. To implement the proposed method, algorithms and software have been developed based on a specific example of the dependence of the water level in the river. The Dniester River weather conditions show that a model built on the basis of the proposed method describes the behavior of complex processes with sufficient accuracy. The resulting empirical model can be used to predict the water level depending on weather conditions.